CHILDFREE MARRIAGE (Perspektif Pemikiran Maqasid Syariah Jaser Audah) - Nur Kamilia (Hakam: Jurnal Kajian Hukum Islam dan Hukum Ekonomi Islam)
In line developments over time, in recent times the choice to refuse pregnancy in marriage (childfree marriage) has spread to all corners of the world. This phenomenon has also spread in Indonesia, and has become a hot topic since influencer Gita Safitri, through uploading her instagram story, stated that she and her husband chosen to be childfree. The effort of this research is to explain the practice of childfree through the perspective of islamic law studies, namely from the perspective Jaser Audah’s maqasid sharia theory. Jaser Audah offers something new to the concept of maqasid sharia through a syistem approach in answering various contempory problems. Meanwhile, data analysis techniques involve carring out editing and editing processes. In the data collection method, the compiler uses the document method and literatur study. The result of this research state that according to Jaser Audah, classical maqasid sharia in more dominatly individual, namely protection and preservation. This needs to be oriented into a maqasid that is more universal, also social and humanitarian in nature (human right) and freedom). From this, it shows that husband and wife the right to decide whether to choose childfree or not in their domestic life.